A preliminary report on the possibilities of price control in Nigeria - Onitiri, H. M. A. (Ibadan : Institute of Social & Economic Research, 1966)
This book reveals the1966 preliminary reports of price control under the findings by the Nigerian institute of social economic research Ibadan.
Includes bibliographical references.
asm 27/02/2019
Loans
Keywords: Price regulation; Prices; Nigeria